Population, social equity and changing production patterns (UN. ECLAC SantiagoCL, 1992)
Outlines the evolution of population dynamics at the regional and country levels. Describes the proposals on changing production patterns with social equity in a context of environmental sustainability and democratic development. Discusses three topics of women and population, and environmental sustainability. Deals with national population policy. Considers international migration and analyses its main implications for the development process. Describes some aspects of the World Population Plan of Action. Provides statistical annex.
Bibliography: 145-153